Bacterial nanocellulose for medical implants - Cherian, Bibin Mathew [UNESP]; Leão, Alcides Lopes [UNESP]; de Souza, Sivoney Ferreira; de Olyveira, Gabriel Molina; Costa, Ligia Maria Manzine; Brandão, Claudia Valeria Seullner [UNESP]; Narine, Suresh S. (Springer Nature, 2013)
Bacterial cellulose (BC) has established to be a remarkably versatile biomaterial and can be used in wide variety of applied scientific endeavours, especially for medical devices. In fact, biomedical devices recently have gained a significant amount of attention because of an increased interest in tissue-engineered products for both wound care and the regeneration of damaged or diseased organs. Due to its unique nanostructure and properties, microbial cellulose is a natural candidate for numerous medical and tissue-engineered applications. Hydrophilic bacterial cellulose fibers of an average diameter of 50 nm are produced by the bacterium Acetobacter xylinum, using a fermentation process. The microbial cellulose fiber has a high degree of crystallinity. Using direct nanomechanical measurement, determined that these fibers are very strong and when used in combination with other biocompatible materials, produce nanocomposites particularly suitable for use in human and veterinary medicine. Moreover, the nanostructure and morphological similarities with collagen make BC attractive for cell immobilization and cell support. The architecture of BC materials can be engineered over length scales ranging from nano to macro by controlling the biofabrication process. The chapter describes the fundamentals, purification and morphological investigation of bacterial cellulose. This chapter deals with the modification of microbial cellulose and how to increase the compatibility between cellulosic surfaces and a variety of plastic materials. Furthermore, provides deep knowledge of fascinating current and future applications of bacterial cellulose and their nanocomposites especially in the medical field, materials with properties closely mimic that of biological organs and tissues were described. © Springer-Verlag Berlin Heidelberg 2013.